Flavonoids eﬀects on the proliferation and protection of Lactobacillus rhamnosus - Busso, Jeﬀerson de Souza; de Sá, Jéssica Maróstica; Fossey, Marcelo Andres; Caruso, Ícaro Putinhon; de Souza, Fátima Pereira (Seven Editora, 2023)
Intestinal microbiota plays an important role in the human organism homeostasis and it is subject to several perturbations caused by diet and environmental factors, inducing dysbiosis. The search for compounds can help rebuild the intestinal microbiota because sometimes this is the only treatment option for intestinal dysbiosis. Phenolic compounds are neutralizing free radicals, showing a mutual relationship with foods rich in ﬂavonoids, so they might be helpful during the restoration of the intestinal microbiota. This study analyzed the direct eﬀect of these compounds on Lactobacillus rhamnosus, cultivated with and without ﬂavonoids in MRS broth, in diﬀerent growth phases and concentrations. After that, were exposed to enzymes that are involved in the human digestive process to analyze any alteration. Flavonoids quercetin, rutin, hesperetin, and hesperidin were individually tested. The results showed that the presence of ﬂavonoids increased the number of colony-forming units (CFU) compared to the control group (without ﬂavonoids), especially when added before the lag phase. In the digestibility test, quercetin showed a minimal eﬀect for the acidic stomach stage, but for the other steps mimicking the further digestive system, there was no diﬀerence compared to the control, all being killed after bile salts. Therefore, we concluded ﬂavonoids are helpful in the proliferation of the tested stain; however, it is necessary to develop more eﬃcient methods so that the ﬂavonoids can overcome the digestive system and reach the intestine with total eﬃciency.DOI:https://doi.org/10.56238/alookdevelopv1-052